Perceived learning needs among coronary artery disease patients: a study in a tertiary hospital - Yaacob, Suriani; Zaini, Noor Hanita; Abdullah, Khatijah Lim; Ahmad, Nor Zehan; Ramoo, Vimala; Mohd Azahar, Nazar Mohd Zabadi; Abdul Aziz, Ahmad Fazli (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Determination of learning needs is central for holistic patient education, to sustain behavior changes and to control patient’s risk factor. However, patients often sense that their learning needs are unmet and information provided was too general. Thus, this study aimed to determine the perceived learning needs and their level of importance among Coronary Artery Disease (CAD) patients. Methods: The current investigation is a descriptive, cross-sectional study for which all CAD patients were selected using the cencus method. The data was collected using Cardiac Patients Learning Needs Inventory. The questionnaire was delivered to 140 CAD patients who had their follow-up in a cardiology clinic. The instrument is reliable with a Cronbach’s alpha coefficient of 0.96. The study design followed STROBE cross-sectional design process guideline. Results: Participants’ mean age was 58.96 ± 9.42 years. More than half of the participants were males (62.9%), employed (52.0%) and had attained secondary level education (69.3%). Around two-thirds (60.7%) of the patients perceived to have high learning needs. Gender and highest educational achievement were significantly associated with perceived learning needs. The most significant perceived learning needs were medication information, risk factors for CAD, information on diet, physical activity, anatomy and physiology, and other related information. Conclusion: This study has identified the important domains of learning needs among CAD patients. Findings from the present study will provide important input for future cardiac educational strategies to reduce the rate of hospital readmission and death.